Measuring the Economic Value of the Sebangau National Park Area in Supporting Sustainable Livelihoods in the Buffer Area, Indonesia - Wiwin Zakiah; Meitiana (Contemporary Research in Business, Management and Economics Vol. 8, 2024)
Forest is a medium for mutual relations between humans and other living things with natural factors, which consist of ecological processes and are a cyclical unit that can support life. Sebangau National Park, one of the Natural Conservation Areas (KPA) in Central Kalimantan, contains tropical peat swamp forests and is the only remaining swamp forest in Central Kalimantan Province. This study aims to calculate the economic value of the Sebangau National Park area in Central Kalimantan Province. The method used in this study is calculating the economic value of the Sebangau National Park area using an economic valuation approach. All the data were collected by using secondary and primary surveys in the form of field observations and interviews with informants so that the data obtained was based on facts. The study results show that the area’s economic value in the Sebangau National Park, Central Kalimantan Province can be demonstrated as the value of the benefits derived from the flora in the Sebangau National Park is Rp 35,247,655,099,086.40 or around 35 trillion rupiahs, with the types of flora that are taken into account, including medicinal plants, ornamental plants, rattan plants and carbon storage (trees). The value of the benefits obtained from the fauna in Sebangau that are taken into account are orangutans, other large mammals, and birds; The total value of the benefits of flora and fauna in Sebangau National Park is Rp 35,984,764,454,951.40 or the equivalent of 36 trillion rupiahs; Based on the results of calculating the value of hill and lake tourism benefits in Sebangau National Park, it can be seen that the total tourism valuation or the total value of tourism benefits in Sebangau National Park. The following is the total tourism valuation of the Sebangau National Park Rp. 107,195,000.00. Henceforth, Sebangau National Park has a valuable ecosystem, so this environment needs to be preserved from illegal logging, forest fires, and other forest exploitation.